2016
DOI: 10.1111/ggi.12787
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between advanced glycation end‐product accumulation and low skeletal muscle mass in Japanese men and women

Abstract: Skin autofluorescence was an independent factor associated with low skeletal muscle index among middle-aged and older Japanese men and women. Geriatr Gerontol Int 2017; 17: 785-790.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 33 publications
1
49
0
1
Order By: Relevance
“…Prior studies have shown that TUG is a good screening tool for sarcopenia among hospitalized older patients and home‐dwelling older adults . Furthermore, AGE is an independent factor of low SMI among middle‐aged and older adults . An experimental study found that mice with high AGE diet showed CML accumulation in their extensor digitorum longus muscle and low muscle strength .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies have shown that TUG is a good screening tool for sarcopenia among hospitalized older patients and home‐dwelling older adults . Furthermore, AGE is an independent factor of low SMI among middle‐aged and older adults . An experimental study found that mice with high AGE diet showed CML accumulation in their extensor digitorum longus muscle and low muscle strength .…”
Section: Discussionmentioning
confidence: 99%
“…The highest quartile of skin AGE levels was correlated with low skeletal muscle mass in older adults . In the studies of participants' skin, AGE was significantly associated with low SMI, incidence of frailty, and low levels of physical activity and functioning . Notably, CML is one type of non‐fluorescent AGE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SAF levels were measured with an AGE Reader (Diag-nOptics Technologies B.V., Groningen, Netherlands) [17]. This noninvasively evaluates the accumulation of AGEs in the skin by measuring the level of fluorescence with light excitation [18].…”
Section: Skin Autofluorescencementioning
confidence: 99%